2020
DOI: 10.3389/fpsyg.2020.01948
|View full text |Cite
|
Sign up to set email alerts
|

On-Field Perceptual-Cognitive Training Improves Peripheral Reaction in Soccer: A Controlled Trial

Abstract: Abilities such as peripheral reaction are of special importance in soccer. Whether these abilities can be improved by sport-specific on-field interventions remains unclear. The aim of the present controlled trial was to investigate the effect of a soccer-specific perceptual-cognitive on-field training on peripheral reaction of highly talented soccer players aged 12-13 years. N = 38 male elite athletes from young talent centers were allocated to an intervention (n = 19) and a control group (CG) (n = 19). Comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Second-division handball players, however, do not have a smaller horizontal visual field after an anaerobic exercise and, to the contrary, showed improved performance in the peripheral perception (in the number of correct reactions and omitted reactions) 163 . Another study, which was published after our systematic search but should nevertheless be noted here, found that perceptual-cognitive training can improve peripheral vision performance—measured with the Vienna Test System before and after the intervention—of young football players 165 …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Second-division handball players, however, do not have a smaller horizontal visual field after an anaerobic exercise and, to the contrary, showed improved performance in the peripheral perception (in the number of correct reactions and omitted reactions) 163 . Another study, which was published after our systematic search but should nevertheless be noted here, found that perceptual-cognitive training can improve peripheral vision performance—measured with the Vienna Test System before and after the intervention—of young football players 165 …”
Section: Resultsmentioning
confidence: 72%
“…163 Another study, which was published after our systematic search but should nevertheless be noted here, found that perceptual-cognitive training can improve peripheral vision performance-measured with the Vienna Test System before and after the intervention-of young football players. 165 Overall, the combination of a foveal and a peripheral task is an elegant way to examine peripheral perception without using eye-tracking fixation control. If people have to fixate on the central display to perform well in a foveal task, participants likely do not use eye movements to detect the peripheral target.…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…An interesting study on how visual stimuli could influence reaction time involved 38 football players who were divided into two groups that followed a 6-month exercise program using Fitlight technology; the authors concluded that the implemented program contributed to the improvement of reaction time [ 61 ]. Studies demonstrated that the relationship between peripheral vision and the optimization of human reactions is determined by brain plasticity, the distance and positioning of the stimulus, the type of sport and the sports experience [ 73 , 74 ]. A series of studies aimed at evaluating agility or reactive speed in handball, volleyball and basketball players or other team games highlighted superior results in basketball and handball players compared to other sports categories [ 2 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems particularly relevant as it has been suggested that practical training approaches should consider ecological validity, transferability, and action-perception coupling [ 29 , 30 , 31 , 32 ]. Along the same theoretical lines, [ 33 ] investigated the effects of cognitive training on sports performance. A careful analysis of the results shows substantial agreement with previously presented experimental evidence [ 12 , 16 , 17 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%